The Role of Leadership Talent Management in Strategic Supremacy: Analytical Research - Munther Sami Qasim, munther sami; Hamed, Suhair (Journal of Economics and Administrative Sciences, 2025)
This paper investigates the impact of leadership talent management on strategic supremacy within medical colleges in the Baghdad governorate. Specifically, this study aims to assess the relationships between the components of leadership talent management, namely development, retention, succession, and motivation, and their roles in achieving strategic advantages. The descriptive-analytical method was employed. Data was collected using a questionnaire-based survey on a sample size of 208 faculty members belonging to selected medical colleges. Analysis was performed using SPSS and AMOS: confirmatory factor analysis, path analysis, and structural equation modeling.Leadership talent management has a positively significant impact on strategic supremacy, according to the findings. The study confirms that leadership development and retention enhance competitive edges held by institutions that allow for medical colleges to keep delivering excellence while adapting to dynamic challenges. Further, the results imply that educational institutions must be required to build a coherent talent management system to ensure the assignment of leadership and nurturing a culture of constant growth.This study fills a certain gap in understanding how leadership talent affects strategic supremacy for academic settings. It will provide insight into how policymakers and administrators can make human capital strategies work more effectively toward achieving institutional objectives. Future research should also investigate other variables that contribute to strategic supremacy and the performance of leadership within higher education.